(untitled) - The World Bank (Jakarta 12240, 2003)
This book is intended to help enhance the participation of women in KDP and other community driven development programs. It describes the experiences of village facilitators (FDs) and kecamata facilitators (FKs) is an effort to overcome the low level of women's participation in the Kecamatan Development program (KDP)
Keywords: Phụ nữ,Women; Ý kiến công luận,Public opinion